Thoracoscopic esophagectomy for thoracic esophageal cancer with right aortic arch and Kommerell diverticulum: a case report and literature review - Yu, Zhao-Jun; Guo, Ling-Wen; Huang, Yang-Yun; Zhao, Lilan; He, Zi-Jie; Pan, Xiao-Jie; Chen, Wen-Shu (Frontiers in Oncology, 2023)
Background Esophageal carcinoma accompanied by a right aortic arch (RAA) is very rare. When combined with Kommerell diverticulum (KD), a right aortic arch forms a vascular ring encircling both the esophagus and trachea. Due to abnormal anatomy of the upper mediastinum, it is very difficult to dissociate the esophagus and its surrounding tissues, especially the left recurrent laryngeal nerve. Herein, we report a case of successful thoracoscopic esophagectomy in an esophageal cancer patient concurrent with a RAA and KD. Case presentation A 62-year-old male patient was diagnosed with esophageal squamous carcinoma in the middle esophagus at clinical stage I (cT1N0M0) according to UICC-TNM classification 8th edition. Further examinations revealed RAA and KD. Based on the three-dimensional CT (3D-CT) reconstruction, a Mckeown esophagectomy via a left thoracoscopic approach in semi-prone position was performed. During the operation, the left recurrent laryngeal nerve was accurately exposed and well protected. Postoperatively, severe complications, including anastomotic leakage and recurrent laryngeal nerve palsy, were not observed. The patient was discharged 12 days after the surgery. Conclusion Preoperative 3D-CT reconstruction is useful to clarify the vascular malformation in esophageal cancer patients with RAA, and helpful to formulate a reasonable surgical approach.